(untitled) (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The objectives of this study are: 1) Want to know the improvement of student learning achievement after the implementation of learning strategies to improve thinking ability, 2) Want to know the influence of student learning motivation after the pakem learning model is applied. This study used action research in two rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and refraining. The target of this study was grade V students of SDN Senakin Seberang. The data obtained are in the form of formative test results, observation sheets for teaching and learning activities. Based on the results of analysts, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (62.5%), cycle II (87.5.00%). The conclusion of this study is that the PAKEM learning model can have a positive effect on the learning motivation of students V SDN Senakin Seberang, and this learning model can be used as an alternative to PAI learning. Keywords: NHT Models, Activities and Learning Outcomes.